The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jace.13927
|View full text |Cite
|
Sign up to set email alerts
|

High Bipolar Fatigue Resistance of BCTZ Lead‐Free Piezoelectric Ceramics

Abstract: (Ba, Ca)(Ti, Zr)O3 ceramics have been considered as a potential lead‐free alternative to commonly used lead‐based piezoelectric ceramics due to their high piezoelectric performance at room temperature. In this study, the bipolar fatigue behavior of this material is investigated at room temperature. Two compositions were cycled with a bipolar electric field signal at 10 Hz with a maximum of three times the coercive field for up to approximately 107 cycles. Both investigated compositions exhibited high bipolar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 54 publications
5
14
0
Order By: Relevance
“…The fatigue behavior of commercial soft PZT ceramics (e.g., PIC151) is also included for further comparison (Figure F) . Several studies previously published reported a very good fatigue resistance in KNN‐CZ5 and BCTZ ceramics (Figure F) . In the present work, a fatigue‐free behavior is obtained at x = 0.2, and that the fatigue resistance of the produced ceramics are either comparable to or better than the aforementioned ceramics.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The fatigue behavior of commercial soft PZT ceramics (e.g., PIC151) is also included for further comparison (Figure F) . Several studies previously published reported a very good fatigue resistance in KNN‐CZ5 and BCTZ ceramics (Figure F) . In the present work, a fatigue‐free behavior is obtained at x = 0.2, and that the fatigue resistance of the produced ceramics are either comparable to or better than the aforementioned ceramics.…”
Section: Resultssupporting
confidence: 61%
“… P ‐ E loops of the ceramics with (A) x = 0, (B) x = 0.2, (C) x = 0.5, (D) x = 0.8 after 10 0 and 10 6 cycles. Comparison of normalized P r of (E) ceramics with different La 3+ contents ( x = 0, 0.2, and 0.5) and (F) several representative lead‐free ceramics and PIC 151 ceramics [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52] Development of these characterisation techniques and predictive modelling covering multiple length scales may be the key tools needed in order to design new reversible phase-change actuator ceramics with improved fatigue properties compared to present generation ceramics. 17,[53][54][55] The present study has shown that minimum grain-scale strain heterogeneity can be achieved by precise control of the lattice distortions of the resultant phases in the transformed state and that this in turn leads to the maximum achievable transformation strain. Designing materials to have controlled combinations of transformation symmetries and unit cell distortions may be challenging.…”
mentioning
confidence: 99%
“…From the above, it is obvious that the mixed phase volume fractions, as well as the average and width of the transformation strain distributions, are intimately linked to the rhombohedral and tetragonal lattice distortions. 55 (e r max ¼ 2.5%), while the tetragonal lattice distortion was modelled assuming the same pseudocubic unit cell a 0 ¼ 3.904 Å for the undistorted reference (initial state BNT-6.25BT, Table I), a constant volume of the distorted tetragonal unit cell (at field value for BNT-6.25BT), and c/a ratios varying in 25 steps between 1.000 (e t max ¼ 0.0%) and 1.038 (e t max ¼ 2.5%). All averages and widths of the transformation strain distributions are reported as fractions of the maximum achievable transformation strain for the particular combination of lattice parameters, thus either for a h111i-oriented rhombohedral or a h100i-oriented tetragonal grain.…”
mentioning
confidence: 99%
“…11,16 Though high strain memory is desired, its stability is more concerned. 12 It is noted that, compared with bipolar cycling, weaker fatigue effect happens under sesquipolar cycling supported by Yao et al 8 and Zhang et al, 18 which may be another reason for the enhanced stability of strain memory. Apparently, the evolution of strain memory vs cycle numbers depends significantly on E À .…”
Section: Resultsmentioning
confidence: 93%